Rescheduling fertilizer nitrogen topdressing timings for improving productivity and mitigating N2O emissions in timely and late sown irrigated wheat (Triticum aestivum L.). Issue 5 (16th April 2021) - Varinderpal-Singh,; Kaur, Satwinderjit; Singh, Jayesh; Kaur, Amandeep; Gupta, R K
ABSTRACT: Three-year multi-location field experiments were conducted in soils of varying inherent nitrogen (N) supply in diverse agro-climatic zones for improving productivity and mitigating N2 O emissions in timely sown and late sown wheat. The biomass, total N uptake (TNU) and spectral properties were monitored at different growth stages. Biomass production and TNU statistics of only 0.76% and 3.4%, respectively, till Zadoks 14 growth stage (four leaves stage) revealed that applying all fertilizer N dose by Zadoks 14 is not an appropriate strategy to assure fertilizer N supply throughout the growth stages. Rescheduled fertilizer N topdressings with moderate N (25 kg ha −1 ) at sowing and remaining N dose in two equal splits at Zadoks 14 and Zadoks 29 (main shoot and 9 more tillers) growth stages reduced N2 O and GHG emissions, respectively, by 32.4% and 30.6%. Sustained N supply till grain filling produced an average of 5.1% to 10.5% higher grain yield and 2.1% to 10.5% higher grain protein content. The spectral properties recorded with PAU-LCC and SPAD meter at Zadoks 29 growth stage governed the grain yield response to fertilizer N application and can be used to fine-tune fertilizer N topdressing decisions over a wide range of varieties, locations, sowing timings and environments.